2011
DOI: 10.1016/j.ccr.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in vanadium catalyzed oxygen transfer reactions

Abstract: Vanadium complexes have proven to be effective catalysts for the activation of peroxides and the selective oxidation of substrates like bromides, sulfides and alkenes. Besides their capability to form metalloperoxo species, which effectively transfer oxygen atoms to the substrate, these systems are synthetically useful for obtaining valuable oxidized molecules on a preparative scale, with a high degree of selectivity and TONs. Furthermore, the use of environmentally friendly oxidants like hydrogen and alkyl hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(52 citation statements)
references
References 100 publications
0
50
0
Order By: Relevance
“…In view of the still increasing power of computational approaches such as the ADF Density Functional Theory package [145], it is also tempting to generate computational structures which can be validated/adjusted in both the EXAFS and XANES part of the X-ray absorption spectrum. and dioxidovanadium (V) stabilized by organic molecules [45,152]. However, recent studies [56] have shown that the influence of the protein stabilization of the active center goes beyond the first coordination sphere.…”
Section: Outlook: Merging Xanes and Exafsmentioning
confidence: 99%
“…In view of the still increasing power of computational approaches such as the ADF Density Functional Theory package [145], it is also tempting to generate computational structures which can be validated/adjusted in both the EXAFS and XANES part of the X-ray absorption spectrum. and dioxidovanadium (V) stabilized by organic molecules [45,152]. However, recent studies [56] have shown that the influence of the protein stabilization of the active center goes beyond the first coordination sphere.…”
Section: Outlook: Merging Xanes and Exafsmentioning
confidence: 99%
“…On the basis of economic and environmental reasons [2,3], oxidation processes with H 2 O 2 are sustainable processes: first of all H 2 O 2 is, besides dioxygen, the most appealing oxidant and the one with the highest "atom efficiency" (47% of active oxygen); in addition, aqueous hydrogen peroxide is readily accessible, safe to use and upon reduction only water is formed [4][5][6][7]. Catalytic systems based on different metals have been employed in conjunction with hydrogen peroxide for oxidation reactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the well-known ability of oxo-vanadium(V) complexes to catalyze oxygen transfer reactions, [20] several orthovanadate derivatives of general composition [V(O)(OR)3] (R = alkyl, aryl or silanyl group) have proven to act as promoters of Meyer-Schuster-type rearrangements. [21] However, they usually operate under high temperature regimes (140-160 ºC) or in the presence of acidic co-catalysts, which limits seriously their synthetic applications.…”
Section: Introductionmentioning
confidence: 81%